Development Potentials of Local Residents for Tourism and Communication Management for Establishment of Sustainable Community Identity of the Tai-Yuan Ethnic Group in Saraburi Province - Dechphol, Punnipa; Northong , Natthacha; Chuawong, Kan (Journal of Roi Et Rajabhat University, 2024)
The objectives of this research were: 1) to study the history of the community, local cultural traditions, archaeological sites, and ancient artifacts with tourism potential of the Tai-Yuan ethnic group; 2) to enhance the capabilities of the local people in tourism management and communication to create a sustainable community identity for the Tai-Yuan ethnic group; and 3) to come up with a particular guideline to create identities and patterns of effective communication to promote sustainable community-based tourism for the Tai-Yuan ethnic group. The research was qualitative in nature, and the data were collected through document synthesis, focus group discussions with 40 key informants, in-depth interviews, and conversations with 40 key informants, including folk philosophers, community leaders and representatives from relevant tourism agencies. The study found that the Tai-Yuan ethnic group had a history and cultural traditions that held significant cultural values, including values in terms of archaeology, history, social aspects, and the environment. The results showed that the development of local people's capabilities led to learning processes, pride in the Tai-Yuan identity, knowledge, and readiness for community-based tourism management. They also gained an understanding of communication methods, patterns, and the importance of communication in creating an identity to enhance sustainable tourism in the community. Four communities in Saraburi province, namely 1) Ban Phraya Tod community in Phraya Tod sub-district, Sao Hai district, 2) Wat Samuhapraditsadaram community in Suan Dok sub-district, Sao Hai district, 3) Khao Kaeo Worawihan community in Ton Tan sub-district, Sao Hai district, and 4) Nong No Tai community in Nong No sub-district, Mueang district, demonstrated readiness in creating effective identities and communication patterns to promote sustainable community-based tourism for the Tai-Yuan ethnic group.